Screen-based behaviour in school-aged children with long-term illness. (December 2015) - Husarova, Daniela; Geckova, Andrea; Blinka, Lukas; Sevcikova, Anna; van Dijk, Jitse; Reijneveld, Sijmen
Abstract Background Evidence is lacking on the screen-based behaviour of adolescents with a chronic condition. The aim of our study was to analyse differences in screen-based behaviour of adolescents by long-term illness, asthma and learning disabilities. Methods We used data from the cross-sectional Health Behaviour of School-aged Children study collected in 2014 among Slovak adolescents (age 13 to 15 years old, N = 2682, 49.7 % boys). We analysed the associations between screen-based behaviour and long-term illness, asthma and learning disabilities using logistic regression models adjusted for gender. Results We found no associations between screen-based behaviour and long-term illness, except that children with asthma had a 1.60-times higher odds of excessively playing computer games than healthy children (95 % confidence interval of odds ratio (CI): 1.11–2.30). Children with learning disabilities had 1.71-times higher odds of risky use of the Internet (95 % CI: 1.19–2.45). Conclusion Adolescents with a long-term illness or with a chronic condition or a learning disability do not differ from their peers in screen-based activities. Exceptions are children with asthma and children with learning disabilities, who reported more risky screen-based behaviour.